A community-based cervical cancer screening program in Alappuzha district of Kerala using camp approach - Lakshmi Mohan; M Karthika (Journal of Family Medicine and Primary Care, 2022)
Background: Cervical cancer is a major cause of preventable cancer related death in women, particularly in middle-income developing countries. Screening of cervical pre-cancer by cytology remains an effective strategy for prevention of mortality. However, there is paucity of community-based studies in Kerala. The aim of this study was to determine the prevalence of cervical precancerous lesions and to study the associated epidemiological factors through camp approach. Materials and Methods: A cross–sectional study was carried out among women in Alappuzha district, Kerala, by conducting community-based screening camps covering all the panchayaths from February 2017 to January 2019. Statistical Analysis Used: Descriptive statistics including mean for continuous variables and frequency along with their percentage for categorical variables were determined. Pearson's Chi-square test was used to determine the strength of the association between variables. Statistical significance was set at P value less than 0.05. Results: Out of 5241 women screened, majority (62.9%) were in the reproductive age group (31–50 years) with mean age of 47.1 ± 10.3 years. The prevalence of precancerous lesions of cervix was 6.37%, which consisted of low-grade squamous intraepithelial lesion (LSIL) in 2.2%, high-grade squamous intraepithelial lesion (HSIL) in 0.5% and Carcinoma-in-situ in 0.2%. Risk factors that had significant association with cervical precancerous lesions were lower education status, genital infections, early marriage age and high parity. Conclusion: Well planned community-based screening programs can help to identify the exact prevalence of cervical pre-cancer in a region and the associated epidemiological factors leading to formulation of effective elimination strategies.